Rubber Plantation Expansion Leads to Increase in Soil Erosion in the Middle Lancang-Mekong River Basin During the Period 2003–2022 - Hongfeng Xu; Tien Dat Pham; Qingquan Wu; Peng Chai; Dengsheng Lu; Dengqiu Li; Yaoliang Chen (Remote Sensing, 2025)
The booming nature rubber industry has contributed to the extensive expansion of rubber plantations in the Lancang-Mekong River Basin over recent decades. To date, limited research has focused on the assessment of soil erosion caused by this expansion, resulting in a knowledge gap in the systematic and quantitative understanding of its ecological and hydrological impacts. This study evaluates soil erosion within rubber plantations and changes associated with their expansion by modifying the Revised Universal Soil Loss Equation (RUSLE) model in the middle section of the Lancang-Mekong River Basin from 2003 to 2022. The results show that: (1) rubber plantations have expanded rapidly, reaching a total area of 70.391 × 104 ha; (2) over the 20-year period, soil erosion trends within rubber plantations show both slight aggravation (affecting 45.377% of the area) and slight mitigation (affecting 35.859% of the area); (3) soil erosion in rubber plantations shows a pattern of decreasing, then increasing, and then decreasing again with stand age, with the lowest erosion (0.693 t·ha−1·yr−1) observed in plantations aged 10–15 years and the highest (1.017 t·ha−1·yr−1) in those aged 15–20 years; (4) rubber plantation expansion led to a fivefold increase in soil erosion with an average soil loss of 0.148 t·ha−1·yr−1 in the non-expansion areas and 0.902 t·ha−1·yr−1 in expansion areas; and (5) slope had the most significant impact on soil erosion. Interactions between slope and other factors —especially slope and soil type (Q > 0.777)—consistently demonstrated strong explanatory power. This research provides valuable insights for the assessment and management of soil erosion in rubber plantations.